Laryngeal histoplasmosis: report of the first case in Colombia - Castro, Luz Angela (Colombia Medica, 2015)
Dear Editor, With regard to the article "Laryngeal histoplasmosis: report of the first case in Colombia" published by Moriones et al. Colomb Med (Cali). 2014; 45(4):186-9 1 , we would like to provide the following comments: Histoplasmosis is a common systemic mycosis in Colombia, and because no reporting requirements exist, a national survey was designed to understand aspects of the disease that could be collected from diagnosed cases to provide useful information. A total of 434 patient surveys from 20 departments were analyzed through 2008; the majority of the reports were from Antioquia, followed by del Valle and Cundinamarca. Thus, the results from these surveys did not indicate that histoplasmosis is more commonly diagnosed in these departments, as the authors had expressed, but rather that these were the most informative departments 2, as this was a voluntary report.